Native and Bioengineered Exosomes for Ischemic Stroke Therapy - Khan, Haroon; Pan, Jia-Ji; Li, Yongfang; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles are natural cell derived vesicles, which are at front foot towards clinical success for various diseases including cerebral ischemia. EVs mediate cell-to-cell communication in different brain cells during both physiological and pathological conditions. Exosome are extensively studied type of EVs, which are considered as the best alternative for stem cells based therapy. They could be secreted by various cell types and have unique biological properties. Even though native exosome have potential for ischemic stroke therapy, some undesirable features prevent their success towards clinical application such as short half-life, poor targeting property, low concentration at target site, rapid clearance from lesion region and inefficient payload. In this review we highlight exosome trafficking and cellular uptake and survey the latest discoveries in context of exosome research as being best fit for brain targeting owing to its natural brain homing abilities. Further we overview the methods how researchers have bioengineered exosome for the stroke therapy. Finally we summarized the studies where exosome was bioengineered by third party for the stroke recovery. This review provide upto date knowledge about versatile nature of exosome with special focus on bioengineered exosome for ischemic stroke therapy. Standard exosome bioengineering techniques are mandatory in future, which will lead exosome towards clinical application in stroke therapy.